Main Technical Characteristics Of Radiation Kilovoltmeter - Tursunboyev Qobiljon Nigmatillayevich; Yusupova Nodira Saidvoris qizi; Odilova Nilufar Jurayeva; Jumanov Shokir Eshimovich (Scholars Digest Publishing, 2023)
The paper considers the results obtained on a personal computer on the basis of the data obtained from the devices for monitoring the radiation and electrical characteristics of X-ray machines, calculating and displaying parameters such as anode voltage on the X-ray tube, exposure dose rate, exposure dose, exposure time, half attenuation layer, a graph of measurement over time and a graph of dose rate measurement from two detectors over time.
Keywords: personal computer, radiation control, X-ray machine, anode voltage, power, detector.